2000
DOI: 10.1016/s0896-6273(00)00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor “DiOlistic” Labeling of the Nervous System Using Lipophilic Dye Combinations

Abstract: We describe a technique for rapid labeling of a large number of cells in the nervous system with many different colors. By delivering lipophilic dye-coated particles to neuronal preparations with a "gene gun," individual neurons and glia whose membranes are contacted by the particles are quickly labeled. Using particles that are each coated with different combinations of various lipophilic dyes, many cells within a complex neuronal network can be simultaneously labeled with a wide variety of colors. This appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
287
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(292 citation statements)
references
References 20 publications
4
287
1
Order By: Relevance
“…The major classes of interneurons, the horizontal, bipolar and amacrine cells can also be subdivided into numerous subpopulations based upon morphological, immunohistochemical and physiological profiles. Using a recently developed method to label cells randomly with lipophilic dyes, referred to as DiOlistics, several groups have classified the retinal interneurons based upon morphology, synaptic location and terminal arborization (Gan et al, 2000;Connaughton et al, 2004). The ability of the lipophilic dyes to freely diffuse within the plasma membrane of the labeled neurons provides a method reminiscent of the Golgi staining so elegantly utilized by Cajal.…”
Section: Retinal Anatomymentioning
confidence: 99%
“…The major classes of interneurons, the horizontal, bipolar and amacrine cells can also be subdivided into numerous subpopulations based upon morphological, immunohistochemical and physiological profiles. Using a recently developed method to label cells randomly with lipophilic dyes, referred to as DiOlistics, several groups have classified the retinal interneurons based upon morphology, synaptic location and terminal arborization (Gan et al, 2000;Connaughton et al, 2004). The ability of the lipophilic dyes to freely diffuse within the plasma membrane of the labeled neurons provides a method reminiscent of the Golgi staining so elegantly utilized by Cajal.…”
Section: Retinal Anatomymentioning
confidence: 99%
“…Cultured SVZ cells were labeled with lipophilic dye coated particles (Gan et al, 2000) before transplantation. The detailed procedure of cell generation and cell labeling has been previously described (Zhang et al, 2003a;Jiang et al, 2005).…”
Section: Generation Of Neural Progenitor Cells and Cell Labelingmentioning
confidence: 99%
“…Recent exciting experiments are beginning to elucidate the mechanisms by which this might occur. By visualizing individual spines using "DiOlistics" (Gan et al, 2000), Wong and colleagues have shown that spontaneous synaptic activity profoundly influences dendritic motility in chick retina . During the period of development when retinal waves are mediated by nAChRs, bath application of nAChR antagonists freezes normally motile dendrites.…”
Section: Role Of Nachr-mediated Waves In Retina Developmentmentioning
confidence: 99%